Application of foliar fertilizer and fungicides on white spot disease control and development of maize - M. V. Faria; R. M. Q. Lana; C. H. Brito; F. B. Agostinho; A. F. Cardoso; A. M. Brandão (Scientific Electronic Archives, 2016)
This study aimed to evaluate the effect of forms of application of foliar fertilizers and fungicides to control fungus causing white maize spot, Phaeosphaeria maydis, and the growth and development of hybrids maize. The design had randomized blocks, with the use two sources hybrids maize with different reaction to white maize spot: resistant and susceptive and application with moisture of foliar chemical fungicide + cobalt foliar + molybdenum foliar + manganese and control treatment, without application consisting of four treatments and five replications. In the treatments with application of moisture were done on vegetative maize growth stage V8 (stage that determine that the number of kernel rows), VT (stage that arrives when the last branch of the tassel is completely visible) and reproductive maize growth stage R2 (kernels are white on the outside and resemble a blister). The evaluation of variables of growth of maize plants: grain dry mass, cob dry mass, leaf dry mass, culm dry mass and modificated leaf ear and total plant dry mass. Harvest was carried out when the grains were 20% humidity. The application of fungicides and foliar fertilizers increased the leaves, culm, ear modificated, cobs and shoot dry mass plants maize. The application of fungicides and foliar fertilizers providing returning of 11.409,5 kg ha-1 of shoot dry mass plants with increased of 1.296 kg ha-1 on soil(12,81%). In the susceptive hybrid maize the application of fungicides and foliar fertilizers provide higher dry mass grains and shoot of plants.